Determination of Screw Withdrawal Strength of Heat-Treated and Reinforced Laminated Veneer Lumber - Osman Perçin (BioResources, 2016)
The withdrawal resistance of screws in heat-treated and reinforced laminated veneer lumber (RLVL) was determined in the radial, tangential, and transverse directions. For this reason, laminated veneer lumber (LVL) and RLVL with carbon fibers were produced from heat-treated oak (Quercus petraea (Liebl.)) veneers using phenol formaldehyde as the adhesive. Wood samples were heat-treated at 140, 170, 200, and 230 °C for 2 h. According to the results of the study, screw withdrawal strength values of LVL increased for heat-treated samples at 140 °C, but decreased at 170, 200, and 230 °C. However, in all groups, the screw withdrawal strength values of the RLVL were higher than those of the LVL. The highest screw withdrawal strength values were identified in the tangential direction, and the lowest were in the transverse directions. Carbon fiber can be used between the heat-treated wood veneers to provide sufficient screw withdrawal strength for use in many different industries.